A shadow detection approach based on fuzzy logic using images obtained from PV array - Karaköse, Mehmet; Firildak, Kazim (Institute of Electrical and Electronics Engineers Inc., 2015)
Shadows on PV arrays influence the energy production performance negatively. There are many methods in the literature related to the detection of these shadows and reconfiguration of arrays. The methods proposed in the literature generally aim at reconfiguration of arrays and detecting shadow regions by using current (I), voltage (V) and power (P) information. In the process of reconfiguration it is quite difficult to measure to use P, V, I information. In this paper, in order to use in the reconfiguration processes for the detection of the shadow region on PV arrays, a new fuzzy logic based computer vision method is presented. The proposed method, firstly, performs object detection with background subtraction. Then, detects the edge of the object regions. Finally, it detects shadow regions with the help of fuzzy logic decision making system. Experimental results are provides effective performance for detecting of shaded areas on PV arrays. © 2015 IEEE.
6th International Conference on Modeling, Simulation, and Applied Optimization, ICMSAO 2015 -- 27 May 2015 through 29 May 2015 -- Istanbul -- 113607
Keywords: Fuzzy Logic; Image Processing; Photovoltaic Arrays; Reconfiguration; Shadow Detection